Fulminant Hepatitis A in Children, its Incidence, Presentation, Complications and Outcome: A Study from Eastern India - Mohanty, Niranjan; Shubhankar, Mishra; Sambedana, Panigrahi (Journal of Nepal Paediatric Society, 2018)
Introduction: Hepatitis A is one of the most frequent infectious liver diseases affecting children worldwide. The disease is usually mild and self-limited, and complications are very rare. But sometimes hepatitis A can cause acute liver failure (ALF), a severe, life-threatening condition. The objective was to do clinicoepidemiological evaluation of hepatitis A patients who were admitted to the In patients department of our hospital along with analyze the complications seen in the disease. Materials and Methods: It was a prospective study, done in Department of paediatrics, Maharaja Krushna Chandra Gajapati from May 2014-April 2016. Total number of patients was 80. Patients having history or features of prodromal symptoms like fever, nausea, vomiting, anorexia, yellowish discoloration of urine and body, pain abdomen, change in mental status and coagulopathy with suspicion of acute hepatitis (within 8 wks) with positive IgM for hepatitis A were included in the group. Statistical analysis was done by SPSS software version 20. Results: Total number of patients was 80. Mean age of hospitalisation was 5.5 years. 90% children were having jaundice. 85% patients were having liver enzyme high. Most common complication was gallbladder wall thickening followed by ascitis, pleural effusion etc. Encephalopathy was observed in three patients. Total three patients died. Maximum death was seen in infancy with delay in hospitalisation. Conclusions: Viral hepatitis due to hepatitis A is a benign disease. But fulminant hepatic failure due to it is not uncommon. The lesser the age, presence of cardinal features like jaundice may not be apparent. So clinicians must be conscious of these lethal complications while managing a child of probable viral hepatitis. This study will raise the consciousness of urgency of vaccination for hepatitis A, which is thought to be sparingly optional for many parents as well as doctors.